THE ANALYSIS OF OPTIMAL PORTFOLIO 3 COMPANIES’ STOCK AND THE INNOVATION OF STOCK PORTFOLIO, PERIOD OF 2014-2016 - Siahaan, Gabriella Grace Yolanda; Siagian, Jhonny (Fundamental Management Journal, 2018)
The purpose of this research was to analyze whether the portfolio of three companies’ stocks are optimal. This research useful for the investors as a consideration to determine the choice of investing in stock portfolio and get the optimal portfolio. Research method is quantitative descriptive method. The research instruments are expected return and risk (standard deviation). The Data is secondary data that used from closing price stocks every month in Indonesia Stocks Exchange. The result of this study indicate that (1) the combination weighted from PT Summarecon Agung Tbk is 10,62%, PT Bank Central Asia Tbk is 62,99% and PT Unilever Indonesia Tbk is 26,39% and give the optimal result. (2) the combination from three companies will give expected return portfolio amount 1,4832 or 1,48% and the risk portfolio amount 0,72 or 72%.Keyword : Expected Return, Standar Deviation and Portfolio